Connectivity analysis of IoV based on scale-free network - Tao HAN; Wei HE; Jun DAI; Yong ZUO; Yang YANG; Xiaohu GE (Tongxin xuebao)
The connectivity of moving vehicles is one of the critical metrics in Internet of vehicles (IoV) that critically influence the performance of data transmission.Due to the high-frequency dynamic changes of the network topology of the IoV, which causes the link to be easily disconnected frequently.It is a critical issue to reduce the probability of link disconnection, and reducing the randomness of link establishment improves the overall network connectivity.To solve the above problems, the network’s connectivity was analyzed under the line of sight path loss model and the interference model, and the dynamic growth (DN) algorithm was designed through the characterization of the IoV link in the real world.Moreover, a scale-free VANET was built through the network’s addition and deletion of nodes and link preference connections.Simulation results indicate that the overall connectivity of the network is improved by 16%.